2013
DOI: 10.1111/vco.12062
|View full text |Cite
|
Sign up to set email alerts
|

Characterization ofHOXgene expression in canine mammary tumour cell lines from spontaneous tumours

Abstract: Spatial/temporal controls of development are regulated by the homeotic (HOX) gene complex and require integration with oncogenes and tumour suppressors regulating cell cycle exit. Spontaneously derived neoplastic canine mammary carcinoma cell models were investigated to determine if HOX expression profiles were associated with neoplasia as HOX genes promote neoplastic potential in human cancers. Comparative assessment of human and canine breast cancer expression profiles revealed remarkable similarity for all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…In the previous study, the HOX gene was overexpressed by investigating the spontaneously derived tumor-bearing canine breast cancer model. The expression profile was consistent with the oncogene-like features (HOXA1, HOXA13, HOXD4, HOXD9 and SIX1) [ 20 ]. It was also reported that HOX cluster genes promoted the proliferation and differentiation of neuroblastoma cells [ 21 ].…”
Section: Introductionmentioning
confidence: 56%
“…In the previous study, the HOX gene was overexpressed by investigating the spontaneously derived tumor-bearing canine breast cancer model. The expression profile was consistent with the oncogene-like features (HOXA1, HOXA13, HOXD4, HOXD9 and SIX1) [ 20 ]. It was also reported that HOX cluster genes promoted the proliferation and differentiation of neuroblastoma cells [ 21 ].…”
Section: Introductionmentioning
confidence: 56%
“…HOXD9 is a little-studied homeobox gene known to be involved in the development of gynecological organs 36 and mammary gland maturation during pregnancy and lactation 37 . Previous reports indicate HOXD9 may behave as an oncogene in glioma 38 and breast cancer 39 . Consistent with this, in functional assays we showed that higher HOXD9 expression reduced apoptosis, increased proliferation under conditions of high cell density and enhances ectopic proliferation of cells in the absence of attachment to a substrate.…”
Section: Discussionmentioning
confidence: 94%
“…The development of disease composed of malignant mammary carcinomas in patients in both species demonstrates similar age-associations, as well as nutritional, environmental, and reproductive factors that correlate with tumorigenesis [73839]. Patients in both species also share similar genetics, histologic appearance, biological behavior, molecular targets, and therapeutic response to treatment [739]. Both human and canine breast cancers exhibit cellular heterogeneity within the tumor and its surrounding environment, and tumors readily develop resistance to existing treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Both species have remarkably similar natural histories, and the patient can die from metastatic disease if not treated effectively [1]. Canine mammary tumors (CMTs) have been characterized extensively, as a comparative model of human breast cancers, and have been shown to have similar genetic defects and phenotypes including hormone-dependence, similar malignant tissue types, and natural history [2345678910].…”
Section: Introductionmentioning
confidence: 99%